Arthur Miller's Death of a salesman - Sterling, Eric, 1963- (Guft va gū ;, 2008)
Arthur Miller¿s Death of a Salesman, the third volume in the Dialogue series, covers six major and controversial topics dealing with Miller¿s classic play. The topics include feminism and the role of women in the drama, the American Dream, business and capitalism, the significance of technology, the legacy that Willy leaves to Biff, and Miller¿s use of symbolism. The authors of the essays include prominent Arthur Miller scholars such as Terry Otten and the late Steven Centola as well as young, emerging scholars. Some of the essays, particularly the ones written by the emerging scholars, tend to employ literary theory while the ones by the established scholars tend to illustrate the strengths of traditional criticism by interpreting the text closely. It is fascinating to see how scholars at different stages of their academic careers approach a given topic from distinct perspectives and sometimes diverse methodologies. The essays offer insightful and provocative readings of Death of a Salesman in a collection that will prove quite useful to scholars and students of Miller¿s most famous play.